SISTEM REKOMENDASI TEMPAT WISATA DI BALI MENGGUNAKAN IMDB WEIGTED RATING DAN CHATBOT - Oktafiana Susanti, Baiq Dwinda; Setiawan, Widyadi; Indra ER, Ngurah (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p9, 2023)
The Bali government is trying to re-optimize Bali's tourism potential after the Covid-19 pandemic. To improve the Balinese economy which had declined during the Covid-19 pandemic where foreign tourist visits decreased by 99.93%. In 2022, the tourism industry in Bali finally recovered with an increase in foreign tourist visits by 12.23%. The Bali government needs to optimize the number of foreign tourist visits to re-optimize the tourism sector. One way that can be done is to improve digital-based information services to introduce Bali to tourists. Therefore, to assist the Bali provincial government in optimizing the tourism sector, a recommendation system for tourist attractions in Bali called "MELALI" was created by utilizing the IMDb Weighted Rating algorithm and equipped with a chatbot as a customer service. Based on the results of system testing using Root Mean Square Error (RMSE), the result is 0.0126 (close to zero), this shows that the model made has a small error rate, besides that the chatbot feature has also been able to identify keywords and provide output in accordance with the requested keywords. Overall the system is running well.